Morphologische und bodenkundliche Beobachtungen in der syrisch-irakischen Wüste - Wirth, Eugen (ERDKUNDE, 1958)
1. The Syrian desert is divided into areas with a relatively dense network of well pronounced waddies, and into areas which are practically level, and without drainage and waddies. The areal distribution of these two types of major landforms is independent of the amount of rainfall, the geology and their location as regards local base levels. The explanation lies in Miocene transgressions and is connected with the deposition in the lower part of the former waddi network. 2. The major landforms of the Syrian desert are determined by a number of erosion surfaces of which the origin of some dates back to the Oligocene. The waddies too, at least as far as their upper courses are concerned, also date from that time. Cuestas and scarps are only found in a few places. 3. In the areas of the Syrian desert without drainage many shallow depressions occur, the origin of which is in no way due to tectonic causes. The present shape of these Khabras is due to karst drainage and deflation. Wind effect in form of corrosion is negligible; the influence of deflation on the major landforms must, however, not be underestimated. 4. Independent from the amount of precipitation, different types of desert, like rock desert, gravel desert, saltclay desert, sand-dune desert, and dust desert, are found in close juxtaposition depending on geology and relief. Similarly as with the desert proper the distribution of the different types of desert steppe also depends on conditions of geology and relief rather than those of climate. 5. The different types of desert proper on the one hand and desert steppe and steppe on the other hand are found in the Syrian desert side by side without difference of climate. It is further impossible to establish a clear distinction between a fossil and more humid and a recent more dry form type. 6. In contrast to north Africa lime crusts are found in the Syrian desert in areas with an annual rainfall of 400—600 mm. In areas with an annual precipitation of 100—300 mm. lime crust formations give way to loose soils rich in lime. 7. The loose soils of the dry regions of northern Arabia are not fossil but are still being formed, and originated by weathering in situ. The formation of loose soils is unrelated to the amount of annual precipitation. 8. The formation of lime crusts is furthered by a material of coarse grain and great permeability, and handicapped by a fine grain and impermeable material. Lime crusts, which are most strongly cemented directly on the surface are formed by capillary action of ground water. Where a crusts is formed as a result of evaporation of rain water it is found in the lower soil horizons while the surface consists of very loose, dusty material. 9. Salt as a geomorphologically effective agent of weathering is of little importance in the Syrian desert since nowhere is the annual precipitation much below 50 mm. Under a strong armour plate of desert lacquer one finds everywhere fresh unweathered rocks. The main factor leading to a loosening of the bedding planes and dustiness of the soils is crystallization of calcite. 10. The proportion of dust in the loose soils of the Syrian desert is largely fixed by a thin zone of the surface where it is baked together, or by dust-skin like phenomena. The notorious dust storms of Mesopotamia originate, generally speaking, not so much in the desert than in the ploughed-up irrigated areas. 11. Many of the marginally situated waddies show clearly the formation of Pleistocene terraces. The waddies in the central areas of the desert have a wide gravel bottom, today safe from flooding; the slopes which lead to this gravel bottom are of relatively young appearance. Thus at least one late-Pleistocene period with deposition of gravel and pronounced lateral erosion must be postulated. For recent and sub-recent times a slight linear down cutting may be discerned at the most; in the majority of cases there is no change at all. 12. There are many indices which indicate that during the Pleistocene there were periods of cooler as well as more humid climate in the Syrian desert. The increase in precipitation may, however, have been relatively little. 13. Overgrazing has done much damage to the vegetation of the steppes and desert steppes. It may be assumed that this is the reason why the possibilities of grazing and tillage without irrigation have deteriorated since Classical times. There is no need to assume climatic changes to explain this deterioration. 14. The propositions and results enumerated in points 1—13 are only valid for the area of the Syrian desert. It seems that the possibilities of establishing general laws of a geomorphology of deserts on the basis of local observations are strictly limited. Each desert area is in many respects an individuality of its own with its own landforms and its own laws for their formation.